YOUNG COCONUT WATER CAN LOWER BLOOD PRESSURE - Prasani, Mutiara; Mekeama, Luri (Jurnal Pendidikan Kesehatan, 2025)
In 2023, it will be found that around 1.28 billion people aged 30-79 years in the world suffer from hypertension. Putri Ayu Health Center, Jambi City, in 2023 there were 4,320 cases. Uncontrolled hypertension will cause complications and even death. One innovation to lower blood pressure is giving young coconut water. To find out about Mrs. R by providing young coconut water to reduce pressure in the working area of ??the Putri Ayu Health Center, Jambi City. The method used in this research is a case report. Researchers provided care for one elderly person, namely Mrs. R who suffers from hypertension. Researchers gave young coconut water to lower blood pressure to Mrs. R in the working area of ??the Putri Ayu Community Health Center, Jambi City. Blood pressure measurements are carried out using a stethoscope and a blood pressure monitor using an observation sheet. Researchers also used SOP guidelines for administering young coconut water. Bleeding care was provided on 8-12 June 2024. Blood pressure on the first day before administration was 170/100 mmHg, and after administration for 3 days it was 145/85 mmHg. Giving young coconut water can reduce blood pressure in hypertensive patients. The community health center is expected to remain active in providing direction and education regarding the importance of maintaining stable blood pressure and complementary therapies to lower blood pressure such as giving young coconut water.